Solvent-free bottom surface integrated anticorrosive paint as well as preparation method and application thereof

Through the integrated anticorrosion coating of solvent-free bottom surface, the synergistic effect of modified fluorocarbon resin and curing agent components is used to solve the problem of complex surface treatment and construction technology of existing steel structure anticorrosion coatings, achieving high adhesion and aging resistance and simplify the effectiveness of construction.

CN119391280APending Publication Date: 2025-02-07ELECTRIC POWER RESEARCH INSTITUTE OF STATE GRID SHANDONG ELECTRIC POWER COMPANY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411488554.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing anticorrosion coatings for steel structures require surface treatment of the steel structure surface, and the construction process is complex, which increases labor and economic costs and reduces construction efficiency.

Method used

It provides a solvent-free bottom integrated anticorrosion coating, which achieves low surface treatment and high adhesion to the steel structure surface through the synergistic effect of modified fluorocarbon resin and curing agent components, reducing construction steps and costs.

Benefits of technology

It realizes low surface treatment of the substrate, improves the adhesion and aging resistance of the coating, simplifies the construction process, reduces economic and labor costs, and improves construction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391280A_ABST
    Figure CN119391280A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings for corrosion protection of steel structures, and particularly relates to a solvent-free bottom surface integrated anticorrosive coating as well as a preparation method and application thereof. Comprising a component A and a component B, the component A comprises the following raw materials in parts by weight: 100 parts of modified fluorocarbon resin, 1-3 parts of an anti-settling agent, 3-6 parts of a corrosion inhibitor, 50-75 parts of an anti-corrosion functional filler and 6-10 parts of an auxiliary agent; the component B comprises the following raw materials in parts by weight: 20-30 parts of a curing agent, 0.01-0.3 part of an acid substance and 0.5-0.8 part of a dehydrating agent. In the coating provided by the invention, the modified fluorocarbon resin and the curing agent component are low in viscosity and are easy to permeate into holes of rusted substances on the surface of a base material so as to coat the rusted substances; furthermore, the strong wettability and flowability of the penetrant further improve the infiltration capacity of the coating system; and finally, the corrosion inhibitor component in the coating and the acid substance in the curing agent can directly react with the corrosion substance, so that the corrosion substance is converted into a passivation substance from enemies to friends. Under the synergistic effect of all the components, coating and conversion of the coating on a corrosion product are achieved, and pretreatment of a base material is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings for corrosion protection of steel structures, and in particular relates to a solvent-free bottom surface integrated anti-corrosion coating and a preparation method and application thereof. Background Art

[0002] Steel structures play a vital role as an indispensable structural material in social construction. However, steel structures used in the atmospheric environment for a long time are corroded by environmental corrosion factors (acidic gases, moisture, oxygen, light, etc.), which affects their structural performance and reduces their service life.

[0003] At present, the anti-corrosion treatment of steel structures in service is mainly based on anti-corrosion coatings, among which solvent-based anti-corrosion coatings account for a large proportion. With the restrictions on VOC (volatile organic compounds) in coatings, solvent-based coatings will gradually be replaced by corresponding environmentally friendly coatings, and solvent-free anti-corrosion coatings are one of them; secondly, before the anti-corrosion maintenance of steel structures, the corrosive substances on their surface need to be treated, and construction treatment can only be carried out after reaching certain standards. Although there are many low-surface treatment anti-corrosion coatings, it is still necessary to remove the floating rust on the surface of the construction object to reach Sa2.5 or St2 level; in addition, the current mainstream construction process is to apply primer first, and then apply topcoat to achieve weather resistance protection of the primer, that is, primer + topcoat or primer + intermediate paint + topcoat, which will increase the economic cost of maintenance and also cause a longer construction period.

[0004] Therefore, existing low-surface or solvent-free coatings still require surface treatment of steel structures, and the weather resistance of the coating is achieved through the combined use of primer and topcoat, which increases labor and economic costs and reduces construction efficiency. Summary of the invention

[0005] In view of the technical deficiencies of existing anti-corrosion coatings for steel structures, the present invention provides a solvent-free bottom-surface integrated anti-corrosion coating.

[0006] The present invention also provides a method for preparing the solvent-free bottom surface integrated anti-corrosion coating.

[0007] The present invention also provides application of the above-mentioned solvent-free bottom surface integrated anti-corrosion coating on the surface of a steel structure.

[0008] In order to solve the above technical problems, the present invention provides the following technical solutions: The present invention provides a solvent-free bottom surface integrated anti-corrosion coating, comprising component A and component B; The component A comprises the following raw materials in parts by weight: 100 parts of modified fluorocarbon resin, 1 to 3 parts of anti-settling agent, 3 to 6 parts of corrosion inhibitor, 50 to 75 parts of anti-corrosion functional filler, and 6 to 10 parts of auxiliary agent; The component B comprises the following raw materials in parts by weight: 20 to 30 parts of a curing agent, 0.01 to 0.3 parts of an acid substance, and 0.5 to 0.8 parts of a dehydrating agent.

[0009] Preferably, the modified fluorocarbon resin is prepared by the following method: (1) Heat and stir trifluorochloroethylene, then dropwise add KH550 silane coupling agent hydrolyzate, and continue to keep warm and stir after the addition is complete to obtain a mixed solution 1; (2) Add KH560 silane coupling agent hydrolyzate to mixed solution 1, and continue to stir while keeping warm after the addition is complete, to obtain mixed solution 2; (3) KH590 silane coupling agent hydrolyzate is added dropwise to the mixed solution 2. After the addition is complete, the mixture is kept warm and stirred. Then the temperature is increased and stirred to obtain a grafted modified trifluorochloroethylene product. The product is then copolymerized with an alkyl vinyl ester to obtain a modified fluorocarbon resin.

[0010] Preferably, in step (1), the mass ratio of chlorotrifluoroethylene to KH550 silane coupling agent hydrolyzate is 10:1; in step (2), the mass ratio of chlorotrifluoroethylene to KH560 silane coupling agent hydrolyzate is 15:1; in step (3), the mass ratio of chlorotrifluoroethylene to KH590 silane coupling agent hydrolyzate is 21:1; and the molar ratio of chlorotrifluoroethylene to alkyl vinyl ester is 1:0.8.

[0011] Preferably, in step (1), the heating stirring is stirring at 65°C for 1 hour; the heat preservation stirring time is 0.5 hour; in step (2), the heat preservation stirring time is 0.5 hour; in step (3), the heat preservation stirring time is 0.5 hour; the heating stirring is stirring at 90°C for 2 hours; the copolymerization reaction conditions are: using modified trifluorochloroethylene and alkyl vinyl ester as synthetic monomers, azobisisobutyronitrile as initiator, the initiator addition amount accounts for 0.8% of the total monomer amount; the reaction is carried out at a pressure of 1.0 MPa and a system temperature of 110°C for 10 hours.

[0012] Preferably, the anti-settling agent is a compound of modified nano-scale silica and polyvinyl alcohol; wherein the modified nano-scale silica is nano-scale silica modified by an aminosilane coupling agent; the mass ratio of the modified nano-scale silica to polyvinyl alcohol is 1:2-3; the particle size of the modified nano-scale silica is less than 35 nm; the corrosion inhibitor is a compound of modified zinc phosphate and modified aluminum tripolyphosphate; wherein the modified zinc phosphate and the modified aluminum tripolyphosphate are both PVP (polyvinyl pyrrolidone) coated; the mass ratio of the modified zinc phosphate to the modified aluminum tripolyphosphate is 1:3-4.

[0013] Preferably, the anti-corrosion functional filler is one or more of zinc powder, modified mica flake iron oxide, flaky aluminum powder, and modified flake graphite; wherein the zinc powder is one or more of spherical zinc powder and flaky zinc powder; the modified mica flake iron oxide is modified with an aminosilane coupling agent; the modified flake graphite is modified with an aminosilane coupling agent; when the anti-corrosion functional filler is a combination of spherical zinc powder and flaky material, the mass ratio of the two is 5 to 10:1.

[0014] Preferably, the auxiliary agent includes a penetrant, a wetting and dispersing agent, a defoaming agent, and an anti-ultraviolet aging agent; the mass ratio of the penetrant, the wetting and dispersing agent, the defoaming agent, and the anti-ultraviolet aging agent is 3~4:2~4:0.5~1:0.5~1; the penetrant is a mixture of fatty alcohol polyoxyethyl ether and glycerol in a mass ratio of 1:1; the wetting and dispersing agent is a compound of a non-ionic surfactant and an anionic surfactant, and the addition mass ratio of the two is 3:1; the defoaming agent is a mineral oil modified polyether defoaming agent; the anti-ultraviolet aging agent is 2-hydroxy-4-n-octyloxybenzophenone.

[0015] Preferably, the curing agent is one or more of toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), and hexamethylene diisocyanate (HDI); the acid substance is one or more of phosphoric acid, phytic acid, tannic acid, and oxalic acid; the dehydrating agent is a low-viscosity ester compound; and the low-viscosity ester compound is BF-5.

[0016] The present invention also provides a method for preparing the above-mentioned solvent-free bottom integrated anti-corrosion coating, comprising the following steps: Preparation of A component coating: (1) First, the anti-corrosion functional filler and the corrosion inhibitor components were weighed according to the formula, and then vacuum dried at 80°C for 1 hour and naturally cooled to room temperature; (2) The dried anti-corrosion functional filler and the corrosion inhibitor component are fully stirred and mixed to obtain a powder mixture; (3) Then add the dust suppressant, corrosion inhibitor and additive into the powder mixture, continue to stir and mix thoroughly, and obtain a secondary mixture; (4) Weigh the modified fluorocarbon resin according to the formula, then heat it to 90°C and stir it for 1 hour, then cool it to 45°C and continue stirring; (5) Slowly add the secondary mixture to the treated modified fluorocarbon resin and continue stirring for 0.5 h, then cool to room temperature, and then grind for 1 h to obtain a grind; (6) After the ground material is stirred and dispersed again for 0.5 h, component A of the coating is obtained and vacuum-filled for standby use; Preparation of component B curing agent: (1) Weigh the curing agent according to the formula, then heat it to 90°C and stir it for 1 hour; then cool it down to 35°C and continue stirring; (2) Slowly add the weighed acid substance according to the formula into the curing agent stirred at 35°C, continue stirring for 0.5h, then add the dehydrating agent in the formula amount, continue stirring for 0.5h, obtain the curing agent B component, and vacuum fill it for standby use.

[0017] The present invention also provides the use of the above-mentioned solvent-free bottom surface integrated anti-corrosion coating on the surface of a steel structure.

[0018] The modified fluorocarbon resin used in the present invention is made of chlorotrifluoroethylene and alkyl vinyl ester as main raw materials, and is grafted by adding hydrolyzed silane coupling agent (KH550, KH560, KH590). The silane-modified fluorocarbon resin contains a certain amount of hydroxyl, epoxy, amino, and mercapto functional groups on its surface, which is easy to form coordination bonds with metal surface materials to improve its adhesion, and the viscosity is less than 4500cps. The specific preparation method is as follows: a certain amount of trifluorochloroethylene is heated to 65°C in a reaction kettle and stirred for 1 hour, then KH550 silane coupling agent hydrolyzate is added dropwise, and the mixture is kept warm and stirred for 0.5 hour after the addition is complete, then KH560 silane coupling agent hydrolyzate is added dropwise, and the mixture is kept warm and stirred for 0.5 hour after the addition is complete, then KH590 silane coupling agent hydrolyzate is added dropwise, and the mixture is kept warm and stirred for 0.5 hour after the addition is complete, then the mixture is heated to 90°C and stirred for 2 hours to obtain a grafted trifluorochloroethylene product, which is then copolymerized with an alkyl vinyl ester to obtain a modified fluorocarbon resin. The silanol and amino groups generated by the hydrolysis of the silane coupling agent after the addition can undergo addition reaction with the carbon-carbon double bond to achieve the purpose of grafting modification.

[0019] When the solvent-free bottom integrated anti-corrosion coating provided by the present invention is applied on the surface of a steel structure, the following steps are included: (1) Treatment of the substrate surface: Use a wire brush or a hair brush or sandpaper with a mesh size not greater than 500 or mechanical sandblasting to clean the loose rust, floating rust and oil stains on the substrate surface; (2) Preparation of coating: Mix coating component A and coating component B thoroughly according to the formula, and let them mature for 5 to 10 minutes before use; (3) Preparation of coating: The prepared coating is applied by rolling, brushing or airless spraying, with two coats applied in each cross direction, and the coating thickness is maintained at 150um~200um; (4) Coating maintenance: After the coating is completely cured, it should be cured for at least 3 days at a temperature greater than -10°C without being damaged by external mechanical forces.

[0020] The solvent-free bottom surface integrated anti-corrosion coating and the coating thereof of the present invention have outstanding comprehensive performance and have the following beneficial effects: (1) Realize low surface treatment of the substrate. First, the modified fluorocarbon resin and curing agent components have low viscosity and are easy to penetrate into the "holes" of the rust on the surface of the substrate to achieve coating; secondly, the strong wettability and fluidity of the penetrant further enhance the penetration ability of the coating system; finally, the corrosion inhibitor components in the coating and the acid substances in the curing agent can directly react with the rust, turning the rust into a passivated product. Under the synergistic effect of the above components, the coating can cover and transform the rust products without the need for pre-treatment of the substrate.

[0021] (2) Excellent adhesion. The hydroxyl, epoxy, amino, and thiol functional groups contained in the modified fluorocarbon resin chain are easy to form coordination bonds with metal surface materials; the corrosion inhibitors in the coating components and the acid substances in the curing agent react with the floating rust products to generate passivation products that convert the loose structure into a hard structure. On the other hand, the corrosion inhibitors in the coating components can also react with the metal substrate to generate metal chelate bonds. The acid substances in the curing agent react with the substrate to produce tiny pitting pits. After the coating penetrates and solidifies, physical and mechanical bonds are formed. In addition, the use of cross-direction brushing and the introduction of flaky materials in the application enhance the interlayer cohesion of the coating. Therefore, under the chemical bonding and physical and mechanical bonding formed by the synergistic effect of the above components, the adhesion of the coating to the substrate is further improved.

[0022] (3) High aging resistance. The carbon chain of the modified fluorocarbon resin is helical, and its CF bond energy is relatively large. The small molecule chain introduced by grafting has a certain shielding effect on the carbon-carbon bond of the main chain, preventing the carbon-carbon bond from breaking and aging. The introduction of flaky materials in the coating system forms a shielding layer in the system. On the one hand, it can shield the internal resin. On the other hand, the reflection of the flaky material on light also reduces the absorption of light by the coating system, improving the aging resistance of the coating for outdoor use. Nano-silica has a high shielding rate against ultraviolet rays. In summary, the coating has high aging resistance.

[0023] (4) Cheap construction. The coating of the present invention realizes the integration of the bottom and the top, and does not need to use a primer + topcoat or a combination of a primer, an intermediate paint and a topcoat, thereby improving the construction efficiency and convenience. The coating of the present invention has extremely low requirements for the treatment of the substrate (the rust removal standard is lower than Sa2.5 or St2), which reduces the pre-treatment process. According to the actual construction requirements, the curing time of the coating system can be adjusted by compounding the curing agent to meet the construction needs. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The coatings of the composite fillers of aluminum and zinc in Example 1 and Comparative Example 3 are shown.

[0025] Specific embodiment The technical solution of the present invention is further explained and illustrated by specific examples. It is worth noting that the raw materials used in the present invention are commercially available unless otherwise specified; the examples only contain part of the content of the present invention.

[0026] The anti-ultraviolet aging agent 2-hydroxy-4-n-octyloxybenzophenone used in the present invention is purchased from BASF C81.

[0027] In some embodiments, the modified fluorocarbon resin is prepared by the following method: (1) Heat trifluorochloroethylene to 65°C, then heat and stir for 1 hour, then dropwise add KH550 silane coupling agent (the mass ratio of trifluorochloroethylene to KH550 silane coupling agent is 10:1) hydrolyzate, and continue to heat and stir for 0.5 hour after the dropwise addition is complete, to obtain a mixed solution 1; (2) Add KH560 silane coupling agent (the mass ratio of trifluorochloroethylene to KH560 silane coupling agent is 15:1) hydrolyzate to the mixed solution 1, and continue to stir and keep warm for 0.5 h after the addition is complete to obtain a mixed solution 2; (3) KH590 silane coupling agent (the mass ratio of trifluorochloroethylene to KH590 silane coupling agent hydrolyzate is 21:1) hydrolyzate is added dropwise to the mixed solution 2. After the addition is complete, the mixture is kept warm and stirred for 2 hours. The temperature is then raised to 90°C and kept warm and stirred for 2 hours to obtain a grafted modified trifluorochloroethylene product. (4) The grafted modified chlorotrifluoroethylene product and alkyl vinyl ester were mixed in a mass ratio of 1:1.2, and then 0.8% of the initiator azobisisobutyronitrile was added to the total monomer amount. The mixture was reacted for 10 h under a pressure of 1.0 MPa and a system temperature of 110°C, and then copolymerized with the alkyl vinyl ester to obtain a modified fluorocarbon resin.

[0028] In some embodiments, the alkyl vinyl ester is selected from vinyl acetate or vinyl methacrylate.

[0029] In the following examples, the modified fluorocarbon resin is prepared by copolymerization of a graft-modified chlorotrifluoroethylene product and vinyl acetate.

[0030] In some embodiments, the present invention provides a method for preparing a solvent-free bottom integrated anti-corrosion coating. The details are as follows: Preparation of A component coating: (1) First, the anticorrosive functional filler and the corrosion inhibitor components were weighed according to the formula, and then placed in a vacuum oven at 80°C for vacuum drying for 1 hour, and then naturally cooled to room temperature; (2) The dried anticorrosive functional filler and the corrosion inhibitor component are fully stirred and mixed in a dry powder mixer for 1 hour to obtain a powder mixture; (3) Then add various additives to the mixed powder (anti-corrosion functional filler and corrosion inhibitor component), and continue to stir and mix with a dry powder mixer for 0.5h to obtain a secondary mixture. (4) Weigh the modified fluorocarbon resin according to the formula, then add it into the heated stirring kettle, heat it to 90°C, heat it with open stirring for 1 hour, cool it down to 45°C and continue stirring; (5) Slowly add the secondary mixture into the treated (4) and continue stirring for 0.5 h, then cool to room temperature, take out and grind in a three-roll mill for 1 h; (6) After the ground material is stirred and dispersed again for 0.5 h, component A of the coating is obtained and vacuum-filled for standby use; Preparation of component B curing agent: (1) Weigh the curing components according to the formula, then place them in a heated stirring kettle, heat to 90°C and stir for 1 hour; then cool to 35°C and continue stirring; (2) Slowly drop the weighed acid substance according to the formula into (1) which is stirred at 35°C, and continue stirring for 0.5 h. Then add the dehydrating agent in the formula and continue stirring for 0.5 h to obtain the curing agent component B, which is then vacuum-filled for standby use.

[0031] In some embodiments, the aminosilane coupling agent modified nano-silica used in the present invention is prepared by the following method: (1) Add nano-silica to a mixed solution of ethanol and water (the mass ratio of silica, ethanol and water is 100:10:1), ultrasonicate for 20 min in a constant temperature water bath at 35°C, and adjust the pH value of the system to 4 with acetic acid to obtain an acidic dispersion; (2) The acidic dispersion in step (1) was heated to 110°C, and an aminosilane coupling agent was added dropwise (1 drop / second, with a drop weight of 10% of the nano-silica), and the mixture was kept warm for 6 hours; (3) The reaction solution of step (2) is centrifuged and washed with ethanol until the supernatant does not change color when ninhydrin is added dropwise, thereby obtaining a precipitate; (4) After the precipitate is ultrasonically dispersed with ethanol, the obtained solution is treated in a vacuum freeze drying oven to obtain aminosilane coupling agent-modified nano-silica.

[0032] In some embodiments, the modified zinc phosphate and the modified aluminum tripolyphosphate are both PVP (polyvinyl pyrrolidone) coated, and the specific modification process is: (1) Add zinc phosphate or aluminum tripolyphosphate to DMF solution (mass ratio 1:10), and ultrasonicate for 20 min in a constant temperature water bath at 35°C to obtain a dispersion; (2) Add polyvinyl pyrrolidone to the DMF solution and ultrasonicate for 20 min in a constant temperature water bath at 35°C to obtain a dispersion. The mass ratio of the two is 1:10. (3) Heat the dispersion from step (1) to 120°C, add the dispersion from step 2 dropwise (1 drop / second, the amount of polyvinyl pyrrolidone added is 15% of the mass of zinc phosphate or aluminum tripolyphosphate), and keep the mixture warm for 8 hours; (4) washing the reaction solution of step (3) by centrifugation with ethanol to obtain a precipitate; (5) After the precipitate is ultrasonically dispersed with ethanol, the obtained solution is treated in a vacuum freeze drying chamber to obtain a modified product.

[0033] In some embodiments, the modified mica flake iron oxide is modified with an aminosilane coupling agent, specifically comprising the following method: (1) adding nano-mica flake iron oxide to a mixed solution of ethanol and water (the mass ratio of nano-mica flake iron oxide, ethanol and water is 100:10:1), ultrasonicating in a constant temperature water bath at 35°C for 20 min, and adjusting the pH value of the system to 4 with acetic acid to obtain an acidic dispersion; (2) The acidic dispersion in step (1) was heated to 110° C., and an aminosilane coupling agent was added dropwise (1 drop / second, with a drop weight of 12% of the mica sheet), and the mixture was kept warm for 6 hours; (3) The reaction solution of step (2) is centrifuged and washed with ethanol until the supernatant does not change color when ninhydrin is added dropwise, thereby obtaining a precipitate; (4) After the precipitate is ultrasonically dispersed with ethanol, the obtained solution is treated in a vacuum freeze drying oven to obtain aminosilane coupling agent-modified mica flake iron oxide.

[0034] In some embodiments, the modified flake graphite is modified with an aminosilane coupling agent, and the specific preparation method is: (1) adding flake graphite to a mixed solution of ethanol and water (the mass ratio of flake graphite, ethanol and water is 100:10:1), ultrasonicating in a constant temperature water bath at 35°C for 20 min, and adjusting the pH value of the system to 4 with acetic acid to obtain an acidic dispersion; (2) The acidic dispersion in step (1) was heated to 110°C, and an aminosilane coupling agent was added dropwise (1 drop / second, with a drop weight of 20% of the flake graphite), and the mixture was kept warm for 6 hours; (3) The reaction solution of step (2) is centrifuged and washed with ethanol until the supernatant does not change color when ninhydrin is added dropwise, thereby obtaining a precipitate; (4) After the precipitate is ultrasonically dispersed with ethanol, the obtained solution is treated in a vacuum freeze drying oven to obtain aminosilane coupling agent-modified flake graphite.

[0035] In some embodiments, the wetting and dispersing agent is a mixture of a nonionic surfactant and an anionic surfactant; the nonionic surfactant is a polyoxyethylene fatty acid ester; and the anionic surfactant is a higher fatty acid salt.

[0036] The defoamer used in the present invention was purchased from BIC of Germany.

[0037] Example 1 Component A: 100 parts of modified fluorocarbon resin, 3 parts of anti-settling agent (including 1 part of modified nano-silica and 2 parts of polyvinyl alcohol), 4 parts of corrosion inhibitor (1 part of modified zinc phosphate and 3 parts of aluminum tripolyphosphate), 60 parts of anti-corrosion functional filler (including 50 parts of spherical zinc powder and 10 parts of flaky zinc powder), 6 parts of additives (including 3 parts of penetrant (1.5 parts of fatty alcohol polyoxyethyl ether and 1.5 parts of glycerol), 2 parts of wetting and dispersing agent (1.5 parts of polyoxyethylene fatty acid ester non-ionic surfactant; 0.5 parts of higher fatty acid salt anionic surfactant), 0.5 parts of defoaming agent and 0.5 parts of anti-ultraviolet aging agent).

[0038] Component B: 25 parts of curing agent (including 10 parts of toluene diisocyanate (TDI) and 15 parts of isophorone diisocyanate (IPDI)), 0.1 parts of acid substances (including 0.05 parts of phosphoric acid, 0.03 parts of phytic acid and 0.02 parts of oxalic acid), 0.6 parts of dehydrating agent BF-5 Comparative Example 1 Compared with Example 1, the modified fluorocarbon resin is replaced with common commercial fluorocarbon resin; the rest is the same as Example 1.

[0039] Comparative Example 2 Compared with Example 1, no penetrant is added, and the rest is the same as Example 1.

[0040] Comparative Example 3 Compared with Example 1, no acid substance is added to the curing agent, and the rest is the same as Example 1.

[0041] Comparative Example 4 Compared with Example 1, the modified fluorocarbon resin is changed to epoxy resin, the curing agent component is changed to epoxy resin (cashew nut shell oil modified phenolic amine curing agent), and the rest remains unchanged.

[0042] Effect Example 1 The coatings prepared in Example 1 and Comparative Examples 1-4 were tested for performance: the specific testing method is: Adhesion test standard: GB 5210-2006 Paint and varnish pull-off adhesion test: Xenon arc light resistance: GB / T 1865-2009 Paints and varnishes, artificial weathering and artificial radiation exposure filtered xenon arc radiation Surface drying and actual drying time: GB 1728-2020 Determination of drying time of paint film and putty film Salt water resistance: GB / T 10834-2008 Determination of salt water resistance of marine paints - Salt water and hot salt water immersion method.

[0043] The specific results are shown in Table 1.

[0044] Preparation of samples to be tested: (1) Treatment of the substrate surface: Use a wire brush to clean the loose rust, floating rust and oil stains on the substrate surface; (2) Preparation of coating: Mix coating component A and coating component B thoroughly according to the formula, and let them mature for 10 minutes before use; (3) Preparation of coating: The prepared coating is applied by rolling, brushing or airless spraying, with two coats applied in each cross direction, and the coating thickness is maintained at 150um~200um; (4) Coating maintenance: After the coating is completely cured, it should be cured for at least 3 days at a temperature greater than -10°C without being damaged by external mechanical forces.

[0045] Table 1 Performance comparison of Example 1 and Comparative Examples 1 to 4 Figure 1 The coatings of the composite fillers of aluminum flakes and zinc flakes of Example 1 and Comparative Example 3 are shown.

[0046] Example 2 Component A: 100 parts of modified fluorocarbon resin, 2 parts of anti-settling agent (including 0.5 parts of modified nano-silicon dioxide and 1.5 parts of polyvinyl alcohol), 5 parts of corrosion inhibitor (1 part of modified zinc phosphate and 4 parts of aluminum tripolyphosphate), 70 parts of anti-corrosion functional filler (including 60 parts of spherical zinc powder and 10 parts of flaky aluminum powder), 6 parts of additives (including 3 parts of penetrant, 2 parts of wetting and dispersing agent, 0.5 parts of defoaming agent and 0.5 parts of anti-ultraviolet aging agent). Component B: 25 parts of curing agent (including 10 parts of toluene diisocyanate (TDI) and 15 parts of isophorone diisocyanate (IPDI)), 0.1 parts of acid substances (including 0.05 parts of phosphoric acid, 0.03 parts of phytic acid and 0.02 parts of oxalic acid), 0.6 parts of dehydrating agent BF-5 Comparative Example 5 Compared with Example 2, nano silicon dioxide is not added, the modified fluorocarbon resin is changed to epoxy resin, the curing agent component is changed to epoxy resin, and the other components remain unchanged.

[0047] Comparative Example 6 Compared with Example 2, only spherical zinc powder is added as the anti-corrosion functional filler, the modified fluorocarbon resin is changed to epoxy resin, the curing agent component is changed to epoxy resin, and the rest remains unchanged.

[0048] Comparative Example 7 Compared with Example 2, the modified fluorocarbon resin is changed to epoxy resin, nano silicon dioxide is not added, and only spherical zinc powder is added as the anti-corrosion functional filler, the curing agent component is changed to epoxy resin, and the rest remains unchanged.

[0049] Effect Example 2 The coatings prepared in Example 2 and Comparative Examples 5-7 were tested for performance, and the specific results are shown in Table 2.

[0050] Table 2 Performance comparison of Example 2 and Comparative Examples 5 to 7

Claims

1. A solvent-free bottom integrated anti-corrosion coating, characterized in that: Comprising component A and component B; The component A comprises the following raw materials in parts by weight: 100 parts of modified fluorocarbon resin, 1 to 3 parts of anti-settling agent, 3 to 6 parts of corrosion inhibitor, 50 to 75 parts of anti-corrosion functional filler, and 6 to 10 parts of auxiliary agent; The component B comprises the following raw materials in parts by weight: 20 to 30 parts of a curing agent, 0.01 to 0.3 parts of an acid substance, and 0.5 to 0.8 parts of a dehydrating agent.

2. The solvent-free bottom integrated anti-corrosion coating according to claim 1, characterized in that: The modified fluorocarbon resin is prepared by the following method: (1) Heat and stir trifluorochloroethylene, then dropwise add KH550 silane coupling agent hydrolyzate, and continue to keep warm and stir after the addition is complete to obtain a mixed solution 1; (2) Add KH560 silane coupling agent hydrolyzate to mixed solution 1, and continue to stir while keeping warm after the addition is complete, to obtain mixed solution 2; (3) KH590 silane coupling agent hydrolyzate is added dropwise to the mixed solution 2. After the addition is complete, the mixture is kept warm and stirred. Then the temperature is increased and stirred to obtain a grafted modified trifluorochloroethylene product. The product is then copolymerized with an alkyl vinyl ester to obtain a modified fluorocarbon resin.

3. The solvent-free bottom integrated anti-corrosion coating according to claim 2, characterized in that: In step (1), the mass ratio of chlorotrifluoroethylene to KH550 silane coupling agent hydrolyzate is 10:1; in step (2), the mass ratio of chlorotrifluoroethylene to KH560 silane coupling agent hydrolyzate is 15:1; in step (3), the mass ratio of chlorotrifluoroethylene to KH590 silane coupling agent hydrolyzate is 21:1; the molar ratio of chlorotrifluoroethylene to alkyl vinyl ester is 1:0.

8.

4. The solvent-free bottom integrated anti-corrosion coating according to claim 2 or 3, characterized in that: In step (1), the heating stirring is stirring at 65°C for 1 hour; the heat preservation stirring time is 0.5 hour; in step (2), the heat preservation stirring time is 0.5 hour; in step (3), the heat preservation stirring time is 0.5 hour; the heating stirring is heating to 90°C and stirring for 2 hours; the copolymerization reaction conditions are: modified trifluorochloroethylene and alkyl vinyl ester are used as synthetic monomers, azobisisobutyronitrile is used as initiator, and the initiator addition amount accounts for 0.8% of the total monomer amount; the reaction is carried out at a pressure of 1.0 MPa and a system temperature of 110°C for 10 hours.

5. The solvent-free bottom integrated anti-corrosion coating according to claim 1, characterized in that: The anti-settling agent is a compound of modified nano-scale silicon dioxide and polyvinyl alcohol; The modified nano-scale silica is aminosilane coupling agent modified nano-scale silica; the mass ratio of the modified nano-scale silica to polyvinyl alcohol is 1:2-3; the particle size of the modified nano-scale silica is less than 35 nm; the corrosion inhibitor is a compound of modified zinc phosphate and modified aluminum tripolyphosphate; The modified zinc phosphate and modified aluminum tripolyphosphate are both PVP-coated; the mass ratio of the modified zinc phosphate to the modified aluminum tripolyphosphate is 1:3-4.

6. The solvent-free bottom integrated anti-corrosion coating according to claim 1, characterized in that: The anti-corrosion functional filler is one or more of zinc powder, modified mica flake iron oxide, flaky aluminum powder, and modified flake graphite; the zinc powder is one or more of spherical zinc powder and flaky zinc powder; the modified mica flake iron oxide is modified by an aminosilane coupling agent; the modified flake graphite is modified by an aminosilane coupling agent; when the anti-corrosion functional filler is a combination of spherical zinc powder and flaky material, the mass ratio of the two is 5 to 10:

1.

7. The solvent-free bottom integrated anti-corrosion coating according to claim 1, characterized in that: The auxiliary agents include penetrant, wetting and dispersing agent, defoamer and anti-ultraviolet aging agent; the mass ratio of the penetrant, wetting and dispersing agent, defoamer and anti-ultraviolet aging agent is 3~4:2~4:0.5~1:0.5~1; the penetrant is a mixture of fatty alcohol polyoxyethyl ether and glycerol in a mass ratio of 1:1; the wetting and dispersing agent is a compound of non-ionic surfactant and anionic surfactant, and the addition mass ratio of the two is 3:1; the defoamer is a mineral oil modified polyether defoamer; the anti-ultraviolet aging agent is 2-hydroxy-4-n-octyloxybenzophenone.

8. The solvent-free bottom integrated anti-corrosion coating according to claim 1, characterized in that: The curing agent is one or more of toluene diisocyanate, isophorone diisocyanate, and hexamethylene diisocyanate; the acid substance is one or more of phosphoric acid, phytic acid, tannic acid, and oxalic acid; the dehydrating agent is a low-viscosity ester compound; and the low-viscosity ester compound is BF-5.

9. A method for preparing the solvent-free bottom integrated anti-corrosion coating according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparation of A-component coating: (1) First, the anti-corrosion functional filler and the corrosion inhibitor components were weighed according to the formula, and then vacuum dried at 80°C for 1 hour and naturally cooled to room temperature; (2) The dried anti-corrosion functional filler and the corrosion inhibitor component are fully stirred and mixed to obtain a powder mixture; (3) Then add the dust suppressant, corrosion inhibitor and additive into the powder mixture, continue to stir and mix thoroughly, and obtain a secondary mixture; (4) Weigh the modified fluorocarbon resin according to the formula, then heat it to 90°C and stir it for 1 hour, then cool it to 45°C and continue stirring; (5) Slowly add the secondary mixture to the treated modified fluorocarbon resin and continue stirring for 0.5 h, then cool to room temperature, and then grind for 1 h to obtain a grind; (6) After the ground material is stirred and dispersed again for 0.5 h, component A of the coating is obtained and vacuum-filled for standby use; Preparation of component B curing agent: (1) Weigh the curing agent according to the formula, then heat it to 90°C and stir it for 1 hour; then cool it down to 35°C and continue stirring; (2) Slowly add the weighed acid substance according to the formula into the curing agent stirred at 35°C, continue stirring for 0.5h, then add the dehydrating agent in the formula amount, continue stirring for 0.5h, obtain the curing agent B component, and vacuum fill it for standby use.

10. Use of the solvent-free bottom integrated anti-corrosion coating as claimed in any one of claims 1 to 8 on the surface of a steel structure.

Citation Information

Patent Citations

  • Epoxy-based solvent-free anticorrosive paint as well as preparation method and use method thereof

    CN118562365A